Optical atomic magnetometry - Gawlik, Wojciech; Pustelny, Szymon (Photonics Letters of Poland, 2009)
This work presents new methods of optical magnetometry developed in the Center for Magneto-Optical Research at the Jagiellonian University. Using rubidium atoms contained in cm-long glass cells and amplitude-modulated laser light, we have recorded magneto-optical signals of extremely small widths. These signals allow measurements of magnetic fields with a sensitivity comparable to that achieved with magnetometers based on Superconducting Quantum Interference Devices (SQUIDs). Full Text: PDF References: M. Faraday,"Experimental Researches in Electricity. Nineteenth Series", Trans. R. Soc. London 136, 1 (1846). [CrossRef] K. Barczak and S. Pustelny,"Magnetooptic properties of special optical type D fibers", J. Phys. IV 137, 15 (2006). [CrossRef] W. Gawlik, J. Kowalski, R. Neumann, and F. Träger," Observation of the electric hexadecapole moment of free Na atoms in a forward scattering experiment", Opt. Commun. 12, 400 (1974). [CrossRef] W. Gawlik, S. Pustelny, in New Trends in Quantum Coherence and Nonlinear Optics, R. Drampyan Ed., 47 (New York, Nova Publishers, 2009). D. Budker, W. Gawlik, D. F. Kimball, S. M. Rochester, A. Weis, and V. V. Yashchuk,"Resonant nonlinear magneto-optical effects in atoms", Rev. Mod. Phys. 74, 1153 (2002). [CrossRef] D. Budker, V.V. Yashchuk, and M. Zolotorev,"Nonlinear Magneto-optic Effects with Ultranarrow Widths", Phys. Rev. Lett. 81(26), 5788 (1998). [CrossRef] D. Budker, D. F. Kimball, S. M. Rochester, V. V. Yashchuk, and M. Zolotorev,"Sensitive magnetometry based on nonlinear magneto-optical rotation", Phys. Rev. A 62, 043403 (2000). [CrossRef] G. Wąsik, W. Gawlik, J. Zachorowski, and W. Zawadzki, "Laser frequency stabilization by Doppler-free magnetic dichroism", Appl. Phys. B 75, 613 (2002). [CrossRef] W. Gawlik, L. Krzemień, S. Pustelny, D. Sangla, J. Zachorowski, M. Graf, A. O. Sushkov, and D. Budker," Nonlinear magneto-optical rotation with amplitude modulated light", Appl. Phys. Lett. 88 131108 (2006). [CrossRef] D. Budker, D. F. Kimball, V. V. Yashchuk, M. Zolotorev,"Nonlinear magneto-optical rotation with frequency-modulated light", Phys. Rev. A 65, 055403 (2002). [CrossRef] J. M. Higbie, E. Corsini, and D. Budker, "Robust, high-speed, all-optical atomic magnetometer", Rev. Sci. Instr. 77, 113106 (2006). [CrossRef] S. Pustelny, A. Wojciechowski, M. Kotyrba, K. Sycz, J. Zachorowski, W. Gawlik, A. Cingoz, N. Leefer, J. M. Higbie, E. Corsini, M. P. Ledbetter, S. M. Rochester, A. O. Sushkov, and D. Budker, "All-optical atomic magnetometers based on nonlinear magneto-optical rotation with amplitude modulated light", Proc. of SPIE 6604, 660404 (2007). [CrossRef] S. Pustelny, A. Wojciechowski, M. Gring, M. Kotyrba, J. Zachorowski, W. Gawlik, "Magnetometry based on nonlinear magneto-optical rotation with amplitude-modulated light", J. Appl. Phys. 103, 063108 (2008). [CrossRef] S. Pustelny, S. M. Rochester, D. F. Jackson Kimball, V. V. Yashchuk, D. Budker, and W. Gawlik, "Nonlinear magneto-optical rotation with modulated light in tilted magnetic fields", Phys. Rev. A 74, 063420 (2006). [CrossRef]